2023
DOI: 10.1371/journal.pone.0273882
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial decline in the ageing old world primate retina: Little evidence for difference between the centre and periphery

Abstract: Mitochondrial decline is a key feature of ageing. The retina has more mitochondria than any other tissue and ages rapidly. To understand human retinal ageing it is critical to examine old world primates that have similar visual systems to humans, and do so across central and peripheral regions, as there is evidence for early central decline. Hence, we examine mitochondrial metrics in young and ageing Macaca fascicularis retinae. In spite of reduced ATP with age, primate mitochondrial complex activity did not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The level of fragmented and degraded mitochondrial DNA (mtDNA) increases significantly [ 89 ]. Finally, the mitochondrial marker Tom20 declines, suggesting that the number of mitochondria declines with age [ 90 ]. Interestingly though, in some studies, the expression and activities of complex I, II, and III did not go down when mitochondria showed other damage, perhaps suggesting a mechanism to compensate for the damage and decline in their number [ 91 ].…”
Section: Mitochondrial State and Vdac Expression With Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of fragmented and degraded mitochondrial DNA (mtDNA) increases significantly [ 89 ]. Finally, the mitochondrial marker Tom20 declines, suggesting that the number of mitochondria declines with age [ 90 ]. Interestingly though, in some studies, the expression and activities of complex I, II, and III did not go down when mitochondria showed other damage, perhaps suggesting a mechanism to compensate for the damage and decline in their number [ 91 ].…”
Section: Mitochondrial State and Vdac Expression With Agingmentioning
confidence: 99%
“…Regarding VDAC expression, Western blots of the whole retinas in young and old macaques showed that while the expression of Tom20 decreased, the expression of VDAC increased with age [ 90 ]. This overexpression of VDAC per mitochondrion might contribute to apoptosis which may explain the reduction in the number of rods in old primates.…”
Section: Mitochondrial State and Vdac Expression With Agingmentioning
confidence: 99%